Managers’ Body Expansiveness, Investor Perceptions, and Firm Forecast Errors and Valuation - DÁVILA, ANTONIO; GUASCH, MARTÍ (Journal of Accounting Research, 2022)
ABSTRACT We examine the relation between a measure of managers’ physical display—body expansiveness—and favorable reporting practices (in firm forecasts and valuation information) and performance (survival and funding success). We videotape 154 entrepreneurs pitching their business ideas, and use computer vision software to obtain information about speakers’ movements. We show that physical expansiveness correlates with higher forecast errors and proposed firm valuations and lower survival rates yet higher likelihood of funding success. We argue that investors may incorrectly interpret nonverbal communication in their assessments of entrepreneurs and propose a behavioral explanation. We further corroborate the proposed mechanism by studying investor perceptions of entrepreneurs’ personal characteristics. Overall, we shed light on an overlooked source of information—nonverbal behavior—and relate it to firm forecasting, valuation, survival, and financing success, which are important factors in the assessment of investment opportunities, deal structure, and monitoring.